In Vitro Bioefficacy Of Rhizobacteria, Isolated From Walnut (Juglans Regia L.) Rhizosphere In North-Western Himalayas, Against Five Fungal Phytopathogens (Applied Biological Research, 2018)
The present study was aimed to assess the bioefficacy of rhizobacteria isolated  from walnut (Juglans regia) grown in North Western Himalayas against five  fungal phytopathogens so that they may, in future, be exploited as biocontrol  agents against fruit crop diseases. Ninety eight rhizobacterial isolates were  isolated from walnut rhizosphere in major walnut growing areas of Kashmir.  The siderophore & HCN production and chitinase activity were detected in  53, 82 and 35 isolates, respectively. In vitro assessment of rhizobacteria for  biocontrol efficacy against 5 fungal pathogens viz., Dematophora necatrix,  Alternaria solani, Pythium aphanidermatum, Fusarium oxysporum and  Phytophthora capsici revealed that most of the rhizobacterial isolates  exhibiting growth inhibition of various fungal pathogens belonged to the  genus Bacillus. In present study, 23, 20, 19, 21 and 20 isolates were found  antagonistic to D. necatrix, A. solani, F. oxysporum, P. aphanidermatum and P.  capsici, respectively, with maximum inhibition in each respective case by  isolate WI 90 (66%), WI 63 (55.6%), WI 62 (43.8%), WI 63 (45.5%) and WI  65 (49%). Twelve most effective isolates were morpho-biochemically and  molecularly characterized and on the basis of 16S rDNA sequencing were  identified as Bacillus licheniformis (isolates WI 90, Bacillus subtilis (isolates WI 63 and WI 65), Bacillus tequilensis (isolate WI 62), Bacillus cereus (isolate  WI 36), Micrococcus luteus (isolates WI 12, WI 41 and WI 80), Micrococcus  yunnanensis (is
Keywords: Biocontrol agents; fungal phytopathogens; PGP attributes; rhizobacteria; walnut